Determinants of health-care costs in the oldest-old in Germany - Brettschneider, Christian; Hajek, Andre; Röhr, Susanne; Fuchs, Angela; Weeg, Dagmar; Mamone, Silke; Werle, Jochen; Heser, Kathrin; Mallon, Tina; Stein, Janine; Pentzek, Michael; Bickel, Horst; et al. (The journal of the economics of ageing, 2019)
The population of the oldest old often suffers from ill health and causes high health care costs. Yet, this group has rarely been examined. We investigated determinants of health care costs in the population of oldest olds (≥85years) in Germany by analyzing data from a large multi-center, prospective cohort study (n=856). Health care costs per capita amounted to 8,023€ (SD: 9637€) in a 6-month period. Costs per capita were highest for inpatient services and nursing care services. Frailty was the dominating factor. In comparison to non-frail people, all degrees of frailty were associated with a similar increase of informal care costs. Morbidity was also associated with increased total costs. Social isolation showed various associations. We conclude that frailty, morbidity and social isolation are the most important factors among the oldest old. As frailty is a common but complex phenomenon in the oldest-old, cost-effective strategies for its management are needed.
Gesehen am 27.02.2020